2016
DOI: 10.1177/0033294116663520
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Lack of Forgiveness and Depression

Abstract: Although an association between lack of forgiveness and poor mental health is known, prior studies have reported mixed findings of the relationship between lack of forgiveness and depressive symptoms. In an attempt to explain the strength differences between lack of forgiveness and depressive symptoms, this study examined the moderating effect of self-compassion. A total of 311 Korean teachers (89 men, 222 women; M age = 39.3 year, SD = 9.1) were asked to complete self-report questionnaires, including the Kore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 42 publications
5
21
0
6
Order By: Relevance
“…In line with our hypotheses, basic hope as well as aspects of forgivingness were inversely related with the level of depression. Our results are consistent with previous findings linking basic hope with depression [13], hope with dispositional forgiveness [31], and forgivingness with depression [51,52]. Moreover, we found evidence supporting the idea that dispositional forgiveness mediates the relationship between hope and depressive symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…In line with our hypotheses, basic hope as well as aspects of forgivingness were inversely related with the level of depression. Our results are consistent with previous findings linking basic hope with depression [13], hope with dispositional forgiveness [31], and forgivingness with depression [51,52]. Moreover, we found evidence supporting the idea that dispositional forgiveness mediates the relationship between hope and depressive symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…"Ben OK değilim-Sen OK'sin" YP' ndaki kişilerin çoğu zaman depresif duygu durumu içinde oldukları belirtilmiştir (Budiša vd., 2012). Depresyonun bireyin affetmesinde de oldukça önemli bir değişken olduğu bilinmektedir (Thoresen vd., 2000;Osterndorf vd., 2011;Chung, 2016). "Ben OK değilim-Sen OK'sin" YP'ye sahip bireyler kendini ve hayatını değerli bulmaz, yoğun olarak değersizlik duygusu yaşarlar.…”
Section: Kendini Affetmeye İlişkin Sonuçlarunclassified
“…Koşulsuz kendini kabul, bireyin onaylanma, ayrılık, başkalarını memnun etme kaygısı taşımamasını ve kendisiyle barışık olmasını sağlayan anksiyete, depresyon olumsuz benlik algısı, somatizasyon ve düşmanlık gibi durumlarla ters yönde ilişkili olan ruh sağlığını koruyucu bir kavramdır (Kapıkıran & Kapıkıran, 2010). Alanyazını incelediğimizde affetmenin de, anksiyete (Baskin ve Enright, 2004;Osterndorf vd., 2011) depresyon (Baskin & Enright, 2004;Osterndorf vd., 2011;Chung, 2016), benlik algısı (Osterndorf vd., 2011) ve düşmanlık (Thompson vd., 2005;Thoresen vd., 2000;Worthington ve Scherer, 2004) gibi kavramlarla ilişkili olduğunu gösteren birçok araştırma bulunmaktadır. Lisans öğrencilerinin affetme düzeylerini, affetme alt boyutlarına göre inceleyen bu araştırmanın sonucuna göre ise koşulsuz kendini kabul değişkenin affetmenin tüm alt boyutlarını (kendini, başkalarını, durumu) pozitif ve anlamlı olarak yordadığı dikkat çekmektedir.…”
Section: Wwwturkishstudiesnet/turkishstudiesunclassified
“…For example, studies of different populations such as college students (Brown, 2003;Orcutt, 2006;Ysseldyk, Matheson, & Anisman, 2007), young people in communities (Toussaint & Webb, 2005) and the elderly (Dezutter, Toussaint, & Leijssen, 2016;Ermer & Proulx, 2016) show that forgiveness significantly predicts depression. In addition, some studies have found that certain variables such as hopelessness (Toussaint, Williams, Musick, & Everson-Rose, 2008), integrity, despair (Dezutter et al, 2016) and self-compassion (Chung, 2016) play an intermediary role in the relationship between forgiveness and depressive symptoms. Therefore, forgiveness plays an important role not only in interpersonal relations, but also in individuals' mental health (e.g., depressive status).…”
Section: Interpersonal Forgiveness and Depressive Symptomsmentioning
confidence: 99%